2012
DOI: 10.1258/jtt.2011.111006
|View full text |Cite
|
Sign up to set email alerts
|

A pilot test of a tailored mobile and web-based diabetes messaging system for adolescents

Abstract: Summary We conducted a pilot trial of a new mobile and web-based intervention to improve diabetes adherence. The text messaging system was designed to motivate and remind adolescents about diabetes self-care tasks. Text messages were tailored according to individually-reported barriers to diabetes self-care. A total of 23 adolescents with type 1 diabetes used the system for a period of three months. On average, they received 10 text messages per week (range 8–12). A matched historical control group from the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 15 publications
1
112
0
Order By: Relevance
“…MED uses the SuperEgo mobile communications platform 18 to tailor and deliver medication adherence promotion text messages and IVR calls to people with diabetes. 17,19 Users receive a daily tailored text message at a random time each day addressing 1 of their 3 highest ranked barriers to adherence (out of 17 assessed).…”
Section: Med Interventionmentioning
confidence: 99%
“…MED uses the SuperEgo mobile communications platform 18 to tailor and deliver medication adherence promotion text messages and IVR calls to people with diabetes. 17,19 Users receive a daily tailored text message at a random time each day addressing 1 of their 3 highest ranked barriers to adherence (out of 17 assessed).…”
Section: Med Interventionmentioning
confidence: 99%
“…15 Text messaging programs present with varying structures, which include text messages created by the research team sent at predetermined times, 9,[12][13][14] text messages based on personal T1D-related goals sent at predetermined times, 11,15 and text messages containing feedback from the medical team in response to participantgenerated texts. 10,13 One recent study 16 combined daily predetermined informational messages with weekly interactive messages related to managing the diabetes regimen.…”
Section: Existing Interventionsmentioning
confidence: 99%
“…10,13 One recent study 16 combined daily predetermined informational messages with weekly interactive messages related to managing the diabetes regimen. In addition, a number of text messaging programs have been combined with other interventions, including changes to insulin regimen, 11 photo diaries, 13 web-based interventions, 12,15 and pedometers; 14 however, no such programs have been combined with in-person behavioral health support.…”
Section: Existing Interventionsmentioning
confidence: 99%
“…A randomized control trial conducted in Netherland on type 2 diabetic patients (207 subjects) to see the improvements in the adherence to treatment by using Real Time Medication Monitoring and mobile text message, found it as an effective method [100]. Recently a study was done in USA to assess the feasibility and acceptance of mobile text message by the diabetic patients and reported positive response was found and it was recommended that its use will prove to be beneficial [101]. One another stud on importance of SMS especially in poor resource setting conducted in India and it was reported that this technique can be used as an innovative approach to fight chronic diseases like type 2 DM [102].…”
Section: Use Of Mobile Phone In the Management Of Diabetesmentioning
confidence: 99%